Experimental data for 'Edge effects in elastic bulging' - Box, F (University of Oxford, 2018)
CSV files contain the experimental data for figure 3 & 8, i.e. bulging profiles and height as a function of uniaxial compression. Material properties and sample dimensions can be found in the Appendix.